Participation of civil society in decisions to mitigate environmental degradation in post-conflict societies: evidence from Somalia. Issue 9 (28th July 2020) - Jama, Osman M.; Liu, Guijian; Diriye, Abdishakur W.; Yousaf, Balal; Basiru, Ibrahim; Abdi, Abdulhakim M.
Abstract : The question of the degree to which participation by civil society contributes to environmental decisions in post-conflict societies has received little attention. This study sheds light on the extent to which degrees of participation contribute to environmental decision-making in the Puntland State of Somalia using questionnaire surveys. We found that active participation has the highest contribution to environmental decisions. Our findings also indicated that the most pressing forms of environmental degradation in Puntland, as perceived by the respondents, are land degradation, drought related to the scarcity of rainfall, and deforestation. This study recommends "environmental cooperation" built into the peace-building process as a clear-cut concept to tackle both environmental degradation and conflicts. At the core of this concept is active participation and collaboration between civil society and the government as a means of mitigating environmental degradation in post-conflict Somalia. This will result in favorable environmental conditions and sustainable peace.